Peran Kepala Sekolah dalam Penerapan Kurikulum KMA Nomor 183 dan Nomor 184 Tahun 2019 di MtSN 3 Jombang - Roziqin, Muhamad Khoirur; Hotima, Nor (Universitas KH. A. Wahab Hasbullah, 2022)
The curriculum as a subject that must be mastered by students, in the planning process has several provisions, one of which is curriculum planning and implementation is determined by the use of learning methods and strategies that allow students to master the subject matter, such as using an expository approach. In implementing the curriculum, especially those under the auspices of the Ministry of Religion, the enactment of the Decree of the Minister of Religion (KMA) Number 183 of 2019 concerning the Islamic and Arabic Language Education Curriculum in Madrasas and the Decree of the Minister of Religion Number 184 concerning Guidelines for Curriculum Implementation in Madrasas. In implementing the curriculum, the principal's role is primarily to create teaching and learning conditions so that teachers and students can learn well. The purpose of this study was to determine the role of the madrasah principal in implementing the KMA Curriculum Number 183 and Number 184 at MTsN 3 Jombang. This type of research is descriptive qualitative, namely research that describes, tells and interprets existing data and produces descriptive data in the form of written/oral words from people and observable behavior and the data are statements. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis technique is descriptive qualitative. Determining the validity of the data, in this study using data triangulation techniques, namely data validity checking techniques that utilize various sources outside the data as comparison material. Based on the results obtained by researchers at MTsN 3 Jombang, that at MTsN 3 Jombang has implemented the latest KMA curriculum. The role of the head in this case is as an educator, school planner, school organizer, establishing school communication, managing school staffing and evaluating schools